2015
DOI: 10.1074/jbc.m114.600569
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of Heparanase Lowers the Amyloid Burden in Amyloid-β Precursor Protein Transgenic Mice

Abstract: Background: Heparan sulfate colocalizes with amyloid-␤ in senile plaques of Alzheimer disease. Results: Overexpression of the heparan sulfate-degrading enzyme (heparanase) lowers the amyloid burden in a transgenic mouse model of Alzheimer disease. Conclusion: Heparan sulfate modulates amyloid-␤ deposition. Significance: We present the first direct in vivo proof that heparan sulfate actively participates in senile plaque formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 33 publications
4
36
0
Order By: Relevance
“…Overexpression of heparanase has been reported to reduce the amyloid load in animal models of other amyloid-related diseases, including AA amyloidosis (20) and Alzheimer disease (37). In this study, we show, for the first time, that overexpression of the HS-degrading enzyme heparanase in pancreatic islets reduces islet amyloid formation.…”
Section: Discussionmentioning
confidence: 54%
“…Overexpression of heparanase has been reported to reduce the amyloid load in animal models of other amyloid-related diseases, including AA amyloidosis (20) and Alzheimer disease (37). In this study, we show, for the first time, that overexpression of the HS-degrading enzyme heparanase in pancreatic islets reduces islet amyloid formation.…”
Section: Discussionmentioning
confidence: 54%
“…HSPGs have been shown to promote Aβ aggregation and fibril formation (16, 26, 41). Thus, we next characterized amyloid plaque load in APP/PS1 and APP/PS1; n Ext1 CKO mice by staining brain sections with Thioflavin S, a fluorescent dye that binds to amyloid fibrils.…”
Section: Resultsmentioning
confidence: 99%
“…A recent study reported that overexpression of heparanase reduces the amyloid burden in a mouse model, likely by modulating Aβ deposition (26). Here, using a conditional mouse model deficient in neuronal HS in adult brain, we bypassed the developmental effects of HS and investigated the cell type-specific roles of HS in amyloid pathogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of HS in the formation of Aβ amyloids in vivo and in vitro has been highlighted by several studies. For instance, transgenic mice overexpressing heparanase showed a decreased number of Aβ amyloid plaques, without alteration on the production and proportion of Aβ40 and Aβ42 peptides . Although residues 12–18 (VHHQKLV) in Aβ40 and Aβ42 are reported as the site of interaction with HS , the anionic bridge between lysine 28 and alanine 42, only present in the Aβ42, was broken by HS .…”
Section: Heparan Sulfates In Alzheimer's Diseasementioning
confidence: 99%